Benzyl N-[(S)-2-hydroxy-1-({[(E)-2-hydroxy-4-methoxybenzylidene] hydrazinyl}carbonyl)ethyl]carbamate - de Souza, M.V.N.; Pinheiro, A.C.; Tiekink, E.R.T.; Wardell, S.M.S.V.; Wardell, J.L. (International Union of Crystallography, 2010)
The shape of the title compound, C19H21N3O6, is curved with the conformation about the imine bond [1.291 (3) angstrom] being E. While the hydroxy-substituted benzene ring is almost coplanar with the hydrazinyl residue [N-N-C-C = 177.31 (18)degrees], an observation correlated with an intramolecular O-H center dot center dot center dot N hydrogen bond leading to an S(6) ring, the remaining residues exhibit significant twists. The carbonyl residues are directed away from each other as are the amines. This allows for the formation of O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds in the crystal, which lead to two-dimensional supramolecular arrays in the ac plane. Additional stabilization to the layers is afforded by C-H center dot center dot center dot pi interactions.